Subjectively perceived change in consumption along the living standards in old ages - Hegedüs, Réka; Rádóczy, Klaudia (Marketing & Menedzsment, 2021)
THE AIMS OF THE PAPER The aim of our research is to provide a picture of the conditions for providing the income background necessary for old age, the spending habits of the 50 plus age group, and to illustrate how the old ages goup of our survey, the elderly age group we survey perceives changes in their spending in the last 10-year. METHODOLOGY We used a representative personal survey with 500 Hungarian people. This survey was made in February 2020 on a targeted sample of the Hungarian population aged 50-70. In the analysis method, we used cluster formation, because we tried to identify groups showing different consumption changes based on the consumption categories of the Hungarian Central Statistical Office. MOST IMPORTANT RESULTS, NEW FINDINGS The results show that the people who participated in the survey had little perception of a change in their spending compared to their life 10 years before. On the other hand, our retirement income in old age may lag far behind the income in active, working years, so we can assume that if the significant decline in income did not affect consumption patterns, old-age income may be supplemented by savings in old age. EMPIRICAL IMPLICATIONS OF THE RESEARCH The clusters that we made shows well that the spendings of the 50-plus age group are also significant for the economy as a whole. The types of their expenditures is diverse and there is a lot of items that they would not necessarily be able to afford from an average income funded by the pension scheme. The characteristics of the clusters also show that there is a positive relationship between financial awareness (planning spending, exploring sales) and age. In our oppinion this is the reason why financial awareness education, the communications about this is very important. The financial management of households can be incorporated into the education of children from an early age. Acknowledgments: This research was partially supported by the Human Resource Development Operational Programme, grant No.: EFOP-3.6.1-16-2016-00004 “Comprehensive developments at the University of Pécs for the implementation of intelligent specialization”